Google Earth for everyone - Stanislao, Nic.; Safari eBooks ([S.l.] : Peachpit Press, 2010)
"This video teaches all Google Earth users the fundmental tools and options for creating and viewing custom content on the globe. Start by learning about Google Earth's navigation, and work your way up to adding your own data to be viewed right within Google Earth. Geared to beginners through advanced users, this video teaches new and powerful techniques in Google Earth."--Resource description page (viewed June 11, 2010).
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title and release information from resource description page (viewed June 11, 2010).
Presenter: Nic Stanislao.
Keywords: Google Earth; Geography -- Computer programs; Geographic information systems; Web search engines; Electronic books